Silicon modified energy storage dielectric film and preparation method thereof
By introducing a small amount of tetraethyl silicate into the polymer dielectric and heat treatment, the crosslinking of the polymer single chain is achieved, which solves the problem of deterioration of the insulation performance of the polymer under high temperature and high electric field conditions, and improves the breakdown resistance and Energy storage density.
Patent Information
- Application Number
- CN202411663643.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-18
AI Technical Summary
The insulation performance of existing polymer dielectrics deteriorates under high temperature and high electric field conditions, and their breakdown resistance is reduced, which affects energy storage density and charge and discharge efficiency.
By introducing a small amount of tetraethyl silicate into the polymer solution, stirring and hydrolysis is carried out to obtain free silicon, and connecting the free silicon with the oxygen element in the single chain of the polymer through heat treatment, the cross-linking of the single chain of the polymer is achieved by heat treatment. , reduce the space and freedom of the molecular chain motion.
Effectively improve the insulation performance of polymers, improve their breakdown strength and energy storage density, and improve high-temperature energy storage performance.
Smart Images

Figure CN119480472A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of dielectric materials, and in particular to a silicon-modified energy storage dielectric film and a preparation method thereof. Background Art
[0002] Polymer dielectric capacitors have ultra-high power density and are widely used in new energy vehicles, aerospace and other fields. Taking the new energy vehicle drive inverter as an example, the ambient temperature is as high as 150°C. Under high temperature and high voltage, the intensified carrier injection and transmission will increase the dielectric energy loss and deteriorate the breakdown strength, thus affecting its energy storage density.
[0003] Currently, the widely used polymers include biaxially oriented polypropylene, polyetherimide, polyimide, etc. Under high temperature and high electric field, the number of carriers inside the polymer increases, the diffusion is accelerated, the conductivity loss is aggravated, the insulation performance is degraded, and its breakdown strength and charge and discharge efficiency are seriously affected, thereby degrading its energy storage density.
[0004] In order to improve the high temperature insulation and low temperature energy storage properties of the above polymers, those skilled in the art consider that silicon dioxide is an inorganic material with excellent insulation properties, and it is expected that the insulation properties of the polymers can be improved by compounding silicon dioxide and polymers. There are two main methods for compounding silicon dioxide and polymers in the prior art. The first method is to introduce silicon dioxide during the preparation of the polymer, and the second method is to prepare a highly insulating SiO2 on the surface of the polymer after the polymer is formed. 2 Inorganic layer. The first method is the inorganic doping method, but for linear polymers, such as polycarbonate, polyetherimide and polyimide, the interface compatibility with inorganic materials is poor, which can easily cause problems such as local electric field concentration. The second method mainly uses magnetron sputtering or plasma chemical vapor deposition to prepare high insulating SiO on the polymer surface. 2 Inorganic layer, although these two methods can effectively inhibit carrier injection and transport, thereby improving the breakdown strength of polymer dielectrics and increasing the energy storage density of polymers, the above methods have the problems of increased preparation difficulty, increased production cost and uneven product quality in the actual production process. Summary of the invention
[0005] In order to solve the above technical problems, the present invention provides a silicon-modified energy storage dielectric film and a preparation method thereof. The present invention uses a polymer solution as a matrix and tetraethyl silicate as a silicon source. A small amount of tetraethyl silicate is introduced into the polymer solution and then stirred, so that the tetraethyl silicate is slowly hydrolyzed by stirring, and the silicon-oxygen bond is broken to obtain free silicon. Subsequently, heat treatment is performed to allow the free silicon to connect with oxygen elements in different polymer chains during the heat treatment process, thereby realizing cross-linking between different polymer chains by connecting multiple polymer chains through silicon elements, thereby effectively reducing the movement space and degree of freedom of the polymer molecular chain, thereby effectively improving the insulation performance of the polymer and improving its breakdown strength.
[0006] The silicon-modified energy storage dielectric film and the preparation method thereof of the present invention are realized by the following technical scheme:
[0007] The first object of the present invention is to provide a method for preparing a silicon-modified energy storage dielectric film, comprising the following steps:
[0008] Step 1, prepare polymer solution:
[0009] The powdered polymer is uniformly dispersed in an organic solvent to obtain a polymer solution.
[0010] It should be noted that the present invention does not limit the specific polymer type, and the corresponding powdered polymer can be selected according to actual needs. For example, in some preferred embodiments of the present invention, the polymer used is one or more of polyetherimide, polycarbonate and polyimide.
[0011] In some preferred embodiments of the present invention, the organic solvent used is one or more of N-methylpyrrolidone, tetrahydrofuran and N-N-dimethylformamide, so that the polymer can be dispersed or dissolved in the organic solvent to avoid subsequent sufficient contact with tetraethyl silicate.
[0012] In some preferred embodiments of the present invention, 0.15 kg to 0.2 kg of the polymer is added per liter of the organic solvent to further ensure that the amount of the organic solvent used can achieve uniform dispersion or dissolution of the polymer.
[0013] Step 2, preparing a mixture of tetraethyl silicate and a polymer solution:
[0014] Tetraethyl silicate is used as a silicon source and added to the polymer solution, and stirred to allow the tetraethyl silicate to hydrolyze in the polymer solution to break chemical bonds and generate free silicon, thereby obtaining a mixed solution.
[0015] Among them, it should be noted that in order to improve the high-temperature insulation and energy storage properties of the polymer, the present invention uses tetraethyl silicate as a silicon source, introduces a small amount of tetraethyl silicate into the polymer solution, and slowly hydrolyzes the tetraethyl silicate under stirring, so that the silicon-oxygen bond is broken to obtain free silicon. The free silicon can connect with oxygen elements in different polymer chains during the subsequent heat treatment process, so that multiple polymer chains are connected through silicon elements to achieve cross-linking between different polymer chains, which can effectively reduce the movement space and freedom of the polymer molecular chain, thereby effectively improving the insulation performance of the polymer and improving its breakdown strength.
[0016] It should be particularly emphasized that the above-mentioned effect can only be achieved by adding a very small amount of tetraethyl silicate to the polymer solution. When the amount of tetraethyl silicate added is too high, too much tetraethyl silicate will hydrolyze to form nano-silicon dioxide. The presence of inorganic nano-silicon dioxide will inevitably cause the problem of poor compatibility of the organic-inorganic interface; and when the amount of tetraethyl silicate added is too small, the insulating properties of the polymer cannot be effectively improved. Therefore, the present invention specifically limits the volume ratio of tetraethyl silicate to the polymer solution to 1:5000 to 50000 to ensure that the added tetraethyl silicate is finally cross-linked with the oxygen on the single polymer chain in the form of free silicon.
[0017] In some preferred embodiments of the present invention, the stirring treatment is carried out at a temperature of 30° C. to 50° C., so that the polymer particles can be dissolved quickly and fully at this temperature.
[0018] In some preferred embodiments of the present invention, the stirring treatment time is 8 hours to 10 hours, so that the polymer particles can be completely dissolved and the polymer and the additive can be fully mixed and uniform.
[0019] In some preferred embodiments of the present invention, the stirring rate of the stirring treatment is 800 r / min to 1500 r / min, so that tetraethyl silicate is slowly hydrolyzed at the stirring rate, thereby breaking the silicon-oxygen bonds to obtain free silicon.
[0020] Step 3, heat treatment:
[0021] The mixed solution is coated on a substrate and then heat treated to allow the obtained free silicon to cross-link with oxygen on a single polymer chain to obtain an energy storage dielectric film precursor.
[0022] It should be noted that the present invention can select a corresponding substrate for coating according to actual needs, such as a clean glass plate as the substrate. When the mixed solution is coated on the substrate, the coating thickness can be selected according to actual needs.
[0023] The present invention does not limit the specific coating method, as long as the mixed liquid can be evenly coated on the substrate. For example, in some preferred embodiments of the present invention, an automatic coater is used for coating, and the coating rate is 10 mm / s to 30 mm / s.
[0024] When performing heat treatment, the present invention preferably adopts a staged and step-by-step heating and insulation method to perform heat treatment, so that free silicon can connect with oxygen elements in different polymer chains during the subsequent heat treatment process, thereby connecting multiple polymer chains through silicon elements to achieve cross-linking between different polymer chains, which can effectively reduce the movement space and freedom of polymer molecular chains, thereby effectively improving the insulation performance of the polymer and improving its breakdown strength.
[0025] In some preferred embodiments of the present invention, the heat treatment is carried out by the following steps:
[0026] First, the temperature is raised to 50°C-70°C and kept at this temperature for 2h-6h; then the temperature is raised to 100°C-150°C and kept at this temperature for 2h-6h; then the temperature is raised to 180°C-220°C and kept at this temperature for 2h-6h, so as to fully volatilize the solvent through a multi-stage step-by-step heating and heat treatment method, while ensuring that the free silicon can be grafted onto the polymer molecular chain.
[0027] Step 4, Drying:
[0028] After the energy storage dielectric film precursor is dried, the silicon-modified energy storage dielectric film is obtained.
[0029] It should be noted that the present invention takes into account the presence of static charge and a small amount of unvolatile solvent on the surface of the energy storage dielectric film precursor after the above-mentioned heat treatment, which will affect its energy storage characteristics. Therefore, the present invention also places the energy storage dielectric film precursor in a vacuum environment and dries it at 150°C to 200°C to remove the static charge on the dielectric surface through vacuum drying and further volatilize the residual solvent, so as to further improve the energy storage characteristics of the material.
[0030] In some preferred embodiments of the present invention, the drying time is 4 hours to 6 hours to ensure that the static charge on the surface of the energy storage dielectric film precursor and the small amount of unvolatile solvent are fully removed.
[0031] The second object of the present invention is a silicon-modified energy storage dielectric film prepared by the above preparation method.
[0032] Compared with the prior art, the present invention has the following beneficial effects:
[0033] The invention uses a polymer solution prepared by adding 0.15kg to 0.2kg of the polymer powder to each liter of the organic solvent as a matrix, tetraethyl silicate as a silicon source, and specifically limits the volume ratio of tetraethyl silicate to the polymer solution to 1:5000 to 50000, so as to avoid the problem that when the amount of tetraethyl silicate added is too high, the tetraethyl silicate will be hydrolyzed to generate nano silicon dioxide, thereby causing poor compatibility of the organic-inorganic interface; and when the amount of tetraethyl silicate added is too small, the problem that the insulation performance of the polymer cannot be effectively improved occurs, so that the amount of tetraethyl silicate added relative to the polymer solution is extremely small, thereby ensuring that the added tetraethyl silicate is slowly hydrolyzed under stirring, and the silicon-oxygen bonds are broken to obtain free silicon. In the subsequent heat treatment process, the free silicon can be connected with the oxygen elements in different polymer chains, so that multiple polymer chains can be connected through silicon elements to achieve cross-linking between different polymer chains, thereby effectively reducing the movement space and freedom of polymer molecular chains, thereby effectively improving the insulation performance of the polymer and improving its breakdown strength. The heat-treated product is then dried to remove the static charge on the surface of the material and a small amount of unvolatile solvent, thereby further improving the insulation performance and breakdown strength of the polymer.
[0034] The preparation method of the present invention can be directly produced by using existing industrialized equipment for producing dielectric films, without the need to replace equipment, and only the processing temperature needs to be controlled, which hardly increases the production cost of the dielectric film. The preparation method of the present invention is simple and easy to operate, and is conducive to promotion and large-scale production.
[0035] The silicon-modified energy storage dielectric film prepared by the present invention has excellent high-temperature insulation performance and high-temperature energy storage performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 The energy storage characteristics test results of the energy storage dielectric films of Example 1 and Comparative Example 1 under different electric field strengths. DETAILED DESCRIPTION
[0037] The technical solutions in the embodiments of the present invention will be described clearly and completely below.
[0038] Example 1
[0039] This embodiment provides a method for preparing a silicon-modified energy storage dielectric film, comprising the following steps:
[0040] Step 1, preparation of polymer solution:
[0041] In this embodiment, polyetherimide powder is used as the polymer powder, N-methylpyrrolidone is used as the organic solvent, and the polyetherimide powder and N-methylpyrrolidone are mixed at a dosage ratio of 1.75 kg:10 L to obtain a polymer solution.
[0042] The molecular structure of the polyetherimide used in this embodiment is shown in Formula 1.
[0043]
[0044] Step 2, preparing a mixture of tetraethyl silicate and a polymer solution:
[0045] According to the volume ratio of tetraethyl silicate to polymer solution of 1:20000, a corresponding amount of tetraethyl silicate was measured, and the measured tetraethyl silicate was added to the polymer solution obtained in the above step 1, followed by stirring with a magnetic stirrer and continuously stirring at 800 r / min for 10 h at 35°C to obtain a mixed solution.
[0046] Step 3, heat treatment:
[0047] A clean glass plate is used as a coating substrate, and the mixed solution obtained in the above step 2 is evenly coated on the clean glass plate at a speed of 20 mm / s using an automatic coater. The glass plate coated with the mixed solution is then placed in an oven, first heated to 60°C, and kept at 60°C for 4 hours; then heated to 120°C, and kept at 120°C for 2 hours; then heated to 200°C, and kept at 2000°C for 2 hours to obtain an energy storage dielectric thin film precursor.
[0048] Step 4, Drying:
[0049] The energy storage dielectric film precursor obtained in the above step 3 is dried at 200° C. for 3 hours to obtain a silicon-modified energy storage dielectric film.
[0050] In the silicon-modified energy storage dielectric film of this embodiment, the molecular structure of the cross-linked two adjacent polymer single chains of silicon and polyetherimide is as shown in Formula 2.
[0051]
[0052] The energy storage dielectric film of this embodiment is recorded as PEI-Si.
[0053] Example 2
[0054] This embodiment provides a method for preparing a silicon-modified energy storage dielectric film, comprising the following steps:
[0055] Step 1, prepare polymer solution:
[0056] In this embodiment, polyetherimide powder is used as the polymer powder, N-methylpyrrolidone is used as the organic solvent, and the polyetherimide powder and N-methylpyrrolidone are mixed at a dosage ratio of 1.75 kg:10 L to obtain a polymer solution.
[0057] Step 2, preparing a mixture of tetraethyl silicate and a polymer solution:
[0058] According to the volume ratio of tetraethyl silicate to polymer solution of 1:50000, a corresponding amount of tetraethyl silicate was measured, and the measured tetraethyl silicate was added to the polymer solution obtained in the above step 1, followed by stirring with a magnetic stirrer and continuously stirring at 800 r / min for 10 h at 35°C to obtain a mixed solution.
[0059] Step 3, heat treatment:
[0060] A clean glass plate is used as a coating substrate, and the mixed solution obtained in the above step 2 is evenly coated on the clean glass plate at a speed of 20 mm / s using an automatic coater. The glass plate coated with the mixed solution is then placed in an oven, first heated to 60°C, and kept at 60°C for 4 hours; then heated to 120°C, and kept at 120°C for 2 hours; then heated to 200°C, and kept at 2000°C for 2 hours to obtain an energy storage dielectric thin film precursor.
[0061] Step 4, Drying:
[0062] The energy storage dielectric film precursor obtained in the above step 3 is dried at 200° C. for 3 hours to obtain a silicon-modified energy storage dielectric film.
[0063] Example 3
[0064] This embodiment provides a method for preparing a silicon-modified energy storage dielectric film, comprising the following steps:
[0065] Step 1, prepare polymer solution:
[0066] In this embodiment, polyetherimide powder is used as the polymer powder, N-methylpyrrolidone is used as the organic solvent, and the polyetherimide powder and N-methylpyrrolidone are mixed at a dosage ratio of 1.75 kg:10 L to obtain a polymer solution.
[0067] Step 2, preparing a mixture of tetraethyl silicate and a polymer solution:
[0068] According to the volume ratio of tetraethyl silicate to polymer solution of 1:30000, a corresponding amount of tetraethyl silicate was measured, and the measured tetraethyl silicate was added to the polymer solution obtained in the above step 1, followed by stirring with a magnetic stirrer and continuously stirring at 800 r / min for 10 h at 35°C to obtain a mixed solution.
[0069] Step 3, heat treatment:
[0070] A clean glass plate is used as a coating substrate, and the mixed solution obtained in the above step 2 is evenly coated on the clean glass plate at a speed of 20 mm / s using an automatic coater. The glass plate coated with the mixed solution is then placed in an oven, first heated to 60°C, and kept at 60°C for 4 hours; then heated to 120°C, and kept at 120°C for 2 hours; then heated to 200°C, and kept at 2000°C for 2 hours to obtain an energy storage dielectric thin film precursor.
[0071] Step 4, Drying:
[0072] The energy storage dielectric film precursor obtained in the above step 3 is dried at 200° C. for 3 hours to obtain a silicon-modified energy storage dielectric film.
[0073] Example 4
[0074] This embodiment provides a method for preparing a silicon-modified energy storage dielectric film, comprising the following steps:
[0075] Step 1, prepare polymer solution:
[0076] In this embodiment, polycarbonate powder is used as the polymer powder, N-methylpyrrolidone is used as the organic solvent, and the polycarbonate powder and N-methylpyrrolidone are mixed at a dosage ratio of 1.5 kg:10 L to obtain a polymer solution.
[0077] Step 2, preparing a mixture of tetraethyl silicate and a polymer solution:
[0078] According to the volume ratio of tetraethyl silicate to polymer solution of 1:10000, a corresponding amount of tetraethyl silicate was measured, and the measured tetraethyl silicate was added to the polymer solution obtained in the above step 1, followed by stirring with a magnetic stirrer and continuously stirring at 800 r / min for 10 h at 35°C to obtain a mixed solution.
[0079] Step 3, heat treatment:
[0080] A clean glass plate is used as a coating substrate, and the mixed solution obtained in the above step 2 is evenly coated on the clean glass plate at a speed of 20 mm / s using an automatic coater. The glass plate coated with the mixed solution is then placed in an oven, first heated to 60°C, and kept at 60°C for 4 hours; then heated to 120°C, and kept at 120°C for 2 hours; then heated to 200°C, and kept at 2000°C for 2 hours to obtain an energy storage dielectric thin film precursor.
[0081] Step 4, Drying:
[0082] The energy storage dielectric film precursor obtained in the above step 3 is dried at 200° C. for 3 hours to obtain a silicon-modified energy storage dielectric film.
[0083] Example 5
[0084] This embodiment provides a method for preparing a silicon-modified energy storage dielectric film, comprising the following steps:
[0085] Step 1, preparation of polymer solution:
[0086] In this embodiment, polyimide powder is used as the polymer powder, N-methylpyrrolidone is used as the organic solvent, and the polyimide powder and N-methylpyrrolidone are mixed at a dosage ratio of 2kg:10L to obtain a polymer solution.
[0087] Step 2, preparing a mixture of tetraethyl silicate and a polymer solution:
[0088] According to the volume ratio of tetraethyl silicate to polymer solution of 1:5000, a corresponding amount of tetraethyl silicate was measured, and the measured tetraethyl silicate was added to the polymer solution obtained in the above step 1, followed by stirring with a magnetic stirrer and continuously stirring at 800 r / min for 10 h at 35° C. to obtain a mixed solution.
[0089] Step 3, heat treatment:
[0090] A clean glass plate is used as a coating substrate, and the mixed solution obtained in the above step 2 is evenly coated on the clean glass plate at a speed of 20 mm / s using an automatic coater. The glass plate coated with the mixed solution is then placed in an oven, first heated to 60°C, and kept at 60°C for 4 hours; then heated to 120°C, and kept at 120°C for 2 hours; then heated to 200°C, and kept at 2000°C for 2 hours to obtain an energy storage dielectric thin film precursor.
[0091] Step 4, Drying:
[0092] The energy storage dielectric film precursor obtained in the above step 3 is dried at 200° C. for 3 hours to obtain a silicon-modified energy storage dielectric film.
[0093] Comparative Example 1
[0094] This comparative example provides a method for preparing an energy storage dielectric film, comprising the following steps:
[0095] Step 1, preparation of polymer solution:
[0096] The polyetherimide powder and N-methylpyrrolidone were mixed at a dosage ratio of 1.75 kg:10 L to obtain a polymer solution.
[0097] Step 2, heat treatment:
[0098] Using an automatic coater, the polymer solution obtained above is evenly coated on a clean glass plate at a speed of 20 mm / s. The glass plate is then placed in an oven, first heated to 60°C and kept at 60°C for 4 hours; then heated to 120°C and kept at 120°C for 2 hours; then heated to 200°C and kept at 200°C for 2 hours to obtain an energy storage dielectric film precursor.
[0099] Step 3, Drying:
[0100] The energy storage dielectric film precursor is dried at 200° C. for 3 hours to obtain the energy storage dielectric film.
[0101] That is, the difference between this comparative example and Example 1 is only that:
[0102] In this comparative example, no tetraethyl silicate was added.
[0103] The energy storage dielectric film of this comparative example is recorded as PEI.
[0104] Experimental Section
[0105] The present invention takes the energy storage dielectric film of Example 1 and Comparative Example 1 as examples, and tests the energy storage characteristics thereof under different electric field strengths, and the test results are as follows: Figure 1 shown.
[0106] Depend on Figure 1 It can be seen that the energy storage dielectric film of Comparative Example 1 can only withstand an electric field strength of 550 MV / m at room temperature, and obtains an electric field strength of 6.07 J / cm 3 The energy storage density of the energy storage dielectric film of Example 1 is 79.51%, and the charge and discharge efficiency under the electric field strength is 660 MV / m at room temperature, which is 20% higher than the electric field strength of the pure PEI energy storage dielectric film of Comparative Example 1. The energy storage dielectric film of Example 1 has a high electric field strength of 8.03 J / cm 3The energy storage density is 1.34W, and its charge and discharge efficiency can still be maintained at 76.64%. This shows that after adding a small amount of tetraethyl silicate, the overall electrical properties of the polymer have been significantly improved.
[0107] The present invention further tests the energy storage characteristics of the energy storage dielectric films prepared in Examples 2 to 5 under different electric field strengths. The test results show that compared with the energy storage dielectric film of Example 1, the amount of tetraethyl silicate added in Example 2 is less, so that although the electric field strength and energy storage density of Example 2 and the examples are improved relative to the pure PEI energy storage dielectric film of Comparative Example 1, the improvement effect is not very obvious. The amount of tetraethyl silicate added in Example 3 is less than that in Example 1, but more than that in Example 2, so that the electric field strength and energy storage density of the pure PEI energy storage dielectric film of Example 3 are improved relative to that of Example 2, but the improvement effect is still not as good as that of Example 1. Compared with the energy storage dielectric film of Example 1, the electric field strength and energy storage density of Examples 4 and 5 are reduced.
[0108] Based on the above, it can be known that the amount of tetraethyl silicate added has an important influence on the performance of the energy storage dielectric film finally formed. When the amount of tetraethyl silicate added is too little or too much, it is not conducive to the improvement of the electric field strength and energy storage density of the energy storage dielectric film. Therefore, the volume ratio of tetraethyl silicate to polymer solution is preferably limited to 1:5000 to 50000 in the present invention to ensure that the energy storage dielectric film prepared by the method of the present invention has excellent high-temperature insulation performance and high-temperature energy storage performance. More preferably, it is 1:2000.
[0109] Obviously, the above embodiments are only some embodiments of the present invention, not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
Claims
1. A method for preparing a silicon-modified energy storage dielectric film, characterized in that: The following steps are involved: The powdered polymer is uniformly dispersed in an organic solvent to obtain a polymer solution; wherein 0.15 kg to 0.2 kg of the polymer is added per liter of the organic solvent; Tetraethyl silicate is used as a silicon source, added to the polymer solution, and stirred to break chemical bonds of the tetraethyl silicate after hydrolysis in the polymer solution, thereby generating free silicon and obtaining a mixed solution; wherein the volume ratio of the tetraethyl silicate to the polymer solution is 1:5000 to 50000; The mixed solution is coated on a substrate and then heat treated to allow the obtained free silicon to cross-link with oxygen on a single polymer chain to obtain an energy storage dielectric film precursor; After the energy storage dielectric film precursor is dried, the silicon-modified energy storage dielectric film is obtained.
2. The preparation method according to claim 1, characterized in that The polymer is one or more of polyetherimide, polycarbonate and polyimide.
3. The preparation method according to claim 1, characterized in that: The organic solvent is one or more of N-methylpyrrolidone, tetrahydrofuran and N-N-dimethylformamide.
4. The preparation method according to claim 1, characterized in that: The heat treatment is carried out by the following steps: First raise the temperature to 50℃~70℃, and keep it at 50℃~70℃ for 2h~6h; Then raise the temperature to 100℃~150℃ and keep it at 100℃~150℃ for 2h~6h; Then raise the temperature to 180℃~220℃ and keep it at 180℃~220℃ for 2h~6h.
5. The preparation method according to claim 1, characterized in that: The temperature of the stirring treatment is 30°C to 50°C.
6. The preparation method according to claim 1, characterized in that: The stirring treatment time is 8h to 10h.
7. The preparation method according to claim 1, characterized in that: The drying temperature of the drying is 50°C to 200°C.
8. The preparation method according to claim 1, characterized in that: The stirring rate of the stirring treatment is 800 r / min to 1500 r / min.
9. A silicon-modified energy storage dielectric film prepared by the preparation method according to any one of claims 1 to 8.